Frederick Street, Port of Spain, Trinidad, B.W.I. - (:unkn) unknown (My University, 2010)
A view of Frederick Street bustling with activity. The tram lines run north to south on the Street. Postcard number 77761.
Colour: Coloured; Style: Landscape; Other: Bordered, Divided
Keywords: Trinidad and Tobago; Postcards; Cities and towns--Trinidad and Tobago--Port of Spain; Signs and signboards--Trinidad and Tobago; Streets--Trinidad and Tobago; Pedestrians--Trinidad and Tobago; Street-railroads--Trinidad and Tobago; Stores, Retail--Trinidad and Tobago; 1948; Automobiles--Trinidad and Tobago; Bicycles--Trinidad and Tobago; Men--Trinidad and Tobago; Women--Trinidad and Tobago; Architecture--Trinidad and Tobago; Frederick Street (Port of Spain)